20-Hydroxyecdysone (20E) Primary Response Gene E93 Modulates 20E Signaling to Promote Bombyx Larval-Pupal Metamorphosis - Liu, Xi (J Biol Chem, 2015)
As revealed in a previous microarray study to identify genes regulated by 20-hydroxyecdysone (20E) and juvenile hormone (JH) in the silkworm, Bombyx mori, E93 expression in the fat body was markedly low prior to the wandering stage but abundant during larval-pupal metamorphosis. Induced by 20E and suppressed by JH, E93 expression follows this developmental profile in multiple silkworm alleles. The reduction of E93 expression by RNAi disrupted 20E signaling and the 20E-induced autophagy, caspase activity, and cell dissociation in the fat body. Reducing E93 expression also decreased the expression of the 20E-induced pupal-specific cuticle protein genes and prevented growth and differentiation of the wing discs. Importantly, the two HTH domains in E93 are critical for inducing the expression of a subset of 20E response genes, including EcR, USP, E74, Br-C, and Atg1. By contrast, the LLQHLL and PLDLSAK motifs in E93 inhibit its transcriptional activity. E93 binds to the EcR-USP complex via a physical association with USP through its LLQHLL motif; and this association is enhanced by 20E-induced EcR-USP interaction, which attenuates the transcriptional activity of E93. E93 acts through the two HTH domains to bind to GAGA-containing motifs present in the Atg1 promoter region for inducing gene expression. In conclusion, E93 transcriptionally modulates 20E signaling to promote Bombyx larval-pupal metamorphosis.